The Implementation of TQM in the Qatari Healthcare Sector - Salaheldin Ismail Salaheldin; Banan A. Mukhalalati (Journal of Accounting, Business and Management (JABM), 2009)
This study aims to examine the implementation of the Total Quality Management (TQM) philosophy in the healthcare sector in a developing nation, i.e. Qatar, in an attempt to determine the most implemented TQM initiatives, the level of understanding and knowledge of TQM and the critical success factors of TQM implementation. Our findings indicated that there is a common understanding between managers about the significance of top management support, employee training and involvement in the TQM implementation; this finding is consistent with earlier studies. Moreover, this study demonstrated the vital role of the supplier in supporting quality improvement that is different between the public and the private sectors. Some theoretical and managerial implications and suggestions for future research are also provided.